Execução das penas privativas de liberdade e suas finalidades: princípio da dignidade humana e a necessidade de desencarceramento - Aith, Marcelo Gurjão Silveira (2024)
The aim of the present work is to study the draconian situation of Brazilian prisons and signal with plausible alternatives to alleviate this unconstitutional state of things, especially by using mechanisms tending to improve the tormenting and sad situation of prison overcrowding. To this end, the very serious problems of overcrowding in Brazilian prisons will be analyzed, consisting of overcrowded prisons in subhuman conditions for the incarcerated. The work will pass, also, by the exam of the purposes of sentencing and the principles that inform penal execution, with the aim of highlighting the unconstitutional state of things in Brazilian prisons and the imperative need of being established serious and agile policies to reduce the prison population. The report by the Public Defender's Office of the State of São Paulo, an important element of research, presents a chaotic scenario of São Paulo's prisons, ranging from overcrowding, passing by the low quality of the food provided, precariousness of the buildings, violence against inmates, among other serious affronts to prisoners' rights. Finally, it will be pointed out the mechanisms needed to reduce the prison population, with the aim of alleviating the affront to the dignity of prisoners